The application of modern management accounting techniques: a field study / Norlaila Abdullah - Abdullah, Norlaila (2009)
This study examines the management accounting (MA) practices adopted by companies in the local industries such as oil and gas, petrochemical, chemical, manufacturing and automobile. A sample comprising 40 local and multinational firms, was measured to determine the rate of adoption of the various MA practices. These practices were further classified as strategic, modem, and conventional for comparative purposes with other countries' emerging development. Some other variables such as production process (technology), production set up, product mix, and firm size (employee) affecting the use and rate of application of MA practices were considered. Findings revealed that firms' usage of the various classes of management accounting practices depended upon the sample origin, size, product lines and technology. Some surprising revelations on the MA applications were highlighted based on the field study conducted.